Psychotropic Medications Use among Children with Autism in Saudi Arabia - Shuliweeh Alenezi; Fahad Alnemary; Asma Alamri; Dalal Albakr; Lamees Abualkhair; Faisal Alnemary (MDPI AG, 2022)
Psychotropic medication use is rising among children with autism spectrum disorders (ASD) in Saudi Arabia. Two hundred ninety-three parents of children diagnosed with ASD completed a parental concerns questionnaire (PCQ) online to examine children's family socio-demographics, health conditions and comorbidities, and past and current exposure to psychotropic medication as prescribed by their primary doctor. Findings revealed that more than one-third of the parents (39.08%) reported that their children were using medications at the time of the survey; risperidone (53%), methylphenidate (30%), and valproic acid (9%) were the most commonly used. A smaller number of parents stated that their children had previously used medications (16.09%). The most often prescribed drugs among this group were risperidone (45%), followed by methylphenidate (32%) and valproic acid (17%). The variables that showed a statistically significant association with the current use of psychotropic drugs were the child's age (OR = 1.25, 95% CI: 1.12, 1.40, p < 0.001), presence of comorbidities (OR = 7.75, 95% CI: 3.48, 17.24, p < 0.001), communication difficulties (OR = 1.79, 95% CI: 1.09, 2.95, p < 0.021), and anxiety symptoms (OR = 1.70, 95% CI: 1.00, 2.87, p < 0.049). Similarly, the child's age (OR = 1.23, 95% CI: 1.08, 1.40, p < 0.002) and presence of comorbidities (OR = 2.83, 95% CI: 1.16, 6.29, p < 0.022) showed statistically significant associations with previous use.